Linguistic features of interjections, onomatopoeic words, and modal words - Kaxarova, Iroda (The Lingua Spectrum, 2026)
In direct and indirect translation between English and Uzbek, interjections, onomatopoeic words, and modal words are sometimes preserved unchanged, while in other cases they are replaced by one another, substituted with different lexical units, or supplemented by words that are absent in the source text. The purpose of this article is to identify the translation features of interjections, onomatopoeic words, and modal words in English and Uzbek from a pragmatic perspective. The study investigates the lexical, morphological-syntactic, functional-semantic, stylistic, poetic, and evaluative characteristics of these word classes in translations from English into Uzbek, as well as the phenomenon of their syncretism. The findings provide theoretical evidence that these linguistic units reflect the distinctive features of the national mentality of the two peoples. The analysis demonstrates that interjections, onomatopoeic words, and modal words perform a variety of artistic and stylistic functions in both languages. In particular, both direct and indirect translations of literary works skillfully employ emotional interjections and onomatopoeic words to convey the psychological state of characters and the communicative situation in a vivid, convincing, and expressive manner. The conclusion emphasizes that interjections, onomatopoeic words, and modal words serve as sources of socio-psychological reaction and perform an important pragmatic function in discourse. Their connotative meaning emerges through the participation of each lexical unit in speech and through its interaction with other linguistic elements. Interjections and onomatopoeic words are frequently used individually, in pairs, or in reduplicated forms, whereas modal words are predominantly used independently. Processes of synonymization are also observed. In translation practice, these units are most commonly rendered through transliteration, equivalent translation, or the selection of appropriate functional correspondences.